Digital, digitalization, digital transition and digital transformation: definitions in question - ELMOUTAOUKIL, ABDELKADER; BELKACEM, CHOKRI (Revue Internationale du Chercheur, 2025)
Abstract At present, the solutions arising from the development of information and communication technologies (ICT) have led to a profound upheaval in the habits, behaviors, and strategies of both individuals and organizations. Indeed, there is a growing — even exponential — interest among researchers in the role played by ICT, digital technologies, and the digital sphere in the economy and society at large. However, somewhat surprisingly, the literature review reveals a certain confusion, even a dichotomy, when it comes to defining the key concepts of this digital revolution — such as digital, digital technologies, digital transition, and digital transformation. Through this article, we aim to examine the definitions of these notions and clarify the boundaries between them. Drawing on a robust literature review, we will present the various definitions attributed to these concepts.